Kiai Nur Iman’s Heritage: Reading the Sunny Muthalib on The Soul Purification - Hadi Imawan, Dzulkifli (Universitas Darussalam Gontor, 2024)
Kyai Nur Iman was one of the great scholars who was influential in the spread of Islam in Java in the 18th-19th century AD. As the son of King Amangkurat IV, Kyai Nur Iman prefers to dedicate his life to teaching the Islamic religion and teaching the concepts of soul purification to society. One of his works examines the purification of the soul entitled the book al-Sunni al-Muthalib. This book is still in the form of a manuscript stored in Pesantren Salimiyah Mlangi in Yogyakarta. This manuscript needs to be scholarly examined because it was written by a 19th century AD scholar who tried to combine two sciences, namely the science of Arabic (nahwu); arabic grammar, and the science of tasawwuf; moral sciene. This study aims to reveal the concept of soul purification explained by Kyai Nur Iman in the manuscriptal-Sunni al-Muttalib. This research method is qualitative research using literature review with historical analysis to explain the concept of soul purification according to Kyai Nur Iman then explains the biography of Kyai Nur Iman. The results of this research explain that the concept of tazkiyah nafs according to Kyai Nur Iman in the book Asna al-mathalib starts with knowing Allah, knowing Rasulullah SAW, and getting to know things that can purify the soul such us repentance, inabah, asceticism, tawakkal, tafwidl, happy and sincere and defile it such us namimah, ghibah, greed, riya', sum'ah, arrogant, ujub, wicked, exposing others' shame, immorality, blasphemy, and wishful thinking.